2005
DOI: 10.1111/j.1572-0241.2005.40859.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Quality of Life in Chronic Pancreatitis Assessed by Structured Interview and the EORTC QLQ-C30 and QLQ-PAN26

Abstract: The EORTC QLQ-C30 and QLQ-PAN26 appear to be an appropriate assessment system for CP, with the addition of items to cover guilt about alcohol consumption, and the burden of abstention. Patients' QoL is adversely affected by the fear of future health problems, difficulty sleeping, and fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
138
2
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(157 citation statements)
references
References 30 publications
4
138
2
13
Order By: Relevance
“…Statement (EL 1b − RG B): Structured questionnaires are useful to evaluate the well-being of patients with chronic pancreatitis. Consensus Levels of Agreement: A+ 50%; A 31.3%; A− 12.5%; D− 6.3%; D 0%; D+ 0% Many structured questionnaires have been utilized to assess the well-being of patients with chronic pancreatitis [20,27,[61][62][63][64][65][66][67][68][69]. SF-12, SF-36, EORTC QLQ C-30, and GIQLI have all been proved useful.…”
Section: C7mentioning
confidence: 99%
“…Statement (EL 1b − RG B): Structured questionnaires are useful to evaluate the well-being of patients with chronic pancreatitis. Consensus Levels of Agreement: A+ 50%; A 31.3%; A− 12.5%; D− 6.3%; D 0%; D+ 0% Many structured questionnaires have been utilized to assess the well-being of patients with chronic pancreatitis [20,27,[61][62][63][64][65][66][67][68][69]. SF-12, SF-36, EORTC QLQ C-30, and GIQLI have all been proved useful.…”
Section: C7mentioning
confidence: 99%
“…1,2,3 It is a progressive and debilitating disease with a long-term prognosis that has been described as dismal. 4 Throughout the illness trajectory there are significant challenges in relation to progression, treatment options and outcomes as well as debilitating intractable pain, steatorrhoea, malabsorption, malnutrition, diabetes mellitus, an increased risk of developing pancreatic cancer and a range of other complications. 3,5 About 50% of patients with CP will undergo surgery to manage their pain or complications; for many, however, despite apparent technical success no measurable improvement is seen in quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been recent recognition of the wider impact of CP on patients' psychological and social well-being, and the burden of living with the condition has been recognised, it is not well documented. 4,6,7 In the majority of QoL studies, the focus was on measuring QoL before and after an intervention and not on comparing QoL in those with chronic pancreatitis and a healthy control group. This suggests that the primary goals for patients with CP are intervention-based, thus perpetuating the notion that interventions are a panacea for QoL issues.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study on patients with pancreatic cancer after evaluation with the eortc QlQ-30 and QlQ-Pan26 revealed that fatigue, loss of appetite and an impaired sense of well-being were troubling them most [32], while questionnaires for patients suffering from chronic pancreatitis revealed a fear of future health problems, sleeping difficulties and fatigue [33] -these symptoms were also present in the patients with pancreatic adenoma participating in the authors' study.…”
Section: Resultsmentioning
confidence: 99%